Doping in Professional Cycling: The Underestimated Organizational Dimensions - Paché, Gilles (Technium Social Sciences Journal, 2022)
The cycling champion Lance Armstrong was at the heart of a doping system that gave rise to one of the most important scandals the sports world has ever known. Numerous studies have been devoted to the topic, adopting a medical, ethical, legal or psychological point of view. However, no research has addressed the organizational dimensions of an extremely sophisticated doping system that allowed Lance Armstrong to win seven successive Tours de France. The objective of this paper is to propose a reflection on these underestimated organizational dimensions, in particular as regards the management of the supply of doping products during the different stages (“étapes”) of the Tours de France. Beyond the specific case of doping in professional cycling, lessons can be drawn on the understanding of the logistical mechanisms related to the traffic of illicit substances.